Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Hippocampus - Cytoarchitecture and Diseases 2022
DOI: 10.5772/intechopen.101309
|View full text |Cite
|
Sign up to set email alerts
|

Neural Circuits and Some New Factors Involved in Hippocampal Memory

Abstract: Humans and other primates have memory, and the hippocampus plays a critical role in this process. The neural circuitry is one of the structural foundations for the hippocampus in exerting memory function. To understand the relationship between the hippocampus and memory, we need to understand neural circuits. Past research has identified several classical neural circuits involved in memory. Although there are challenges with the study of hippocampal neural circuits, research on this topic has continued, and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 116 publications
0
1
0
Order By: Relevance
“…Furthermore, animal research has shown that in stark difference to the classical canonical microcircuits in the neocortex, differentiating feedforward and feedback pathways 2 , the hippocampal projections are primarily feedforward. Nevertheless, inputs to hippocampal pyramidal cells can be differentiated based on their position along the dendritic tree (a schematic depiction is given in supplementary figure S1): While synaptic connections along the "trisynaptic pathway" [3][4][5] (entorhinal cortex (EC) → DG → CA3 → CA1) terminate at perisomatic CA3 and CA1 layers (i.e., St. pyramidale and St. radiatum), direct EC projections terminate at distal apical dendrites (in St. lacunosum-moleculare) of CA1 and CA3; CA3 receives additional input to proximal apical dendrites via its abundant recurrent collaterals 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, animal research has shown that in stark difference to the classical canonical microcircuits in the neocortex, differentiating feedforward and feedback pathways 2 , the hippocampal projections are primarily feedforward. Nevertheless, inputs to hippocampal pyramidal cells can be differentiated based on their position along the dendritic tree (a schematic depiction is given in supplementary figure S1): While synaptic connections along the "trisynaptic pathway" [3][4][5] (entorhinal cortex (EC) → DG → CA3 → CA1) terminate at perisomatic CA3 and CA1 layers (i.e., St. pyramidale and St. radiatum), direct EC projections terminate at distal apical dendrites (in St. lacunosum-moleculare) of CA1 and CA3; CA3 receives additional input to proximal apical dendrites via its abundant recurrent collaterals 6 .…”
Section: Introductionmentioning
confidence: 99%